Juridical Review of the Merger of Gojek and Tokopedia in the Aspect of Unfair Business Competition - Naufal Tunggul Alam (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Mergers in digital companies are things that have recently become a topic of discussion, concerns about indications of monopolistic practices in them are one of them. As in the merger activity of the digital companies Gojek and Tokopedia which attracted a lot of attention. KPPU is considered to have an indispensable role in supervising and assessing merger activities that have the potential to create a monopoly, especially in digital company mergers. The purpose of this paper is to find out the regulation, supervision, and evaluation by KPPU of monopoly practices in digital company mergers. This writing uses the approach of legislation. The result of this writing is that KPPU has not found any monopolistic practices in the merger of Gojek and Tokopedia companies, by prioritizing analysis of assessment aspects such as aspects of market concentration using the HHI method, barriers to market entry, and potential anti-competitive behavior. With the merger of the GoTo group, access to market share for new digital companies engaged in the same field has not experienced any obstacles at all, nor has there been any discriminatory policy imposed by the GoTo group in carrying out its business against competitors.